Frustrated Lewis Pair Catalysed Reactions - Zhou, Rundong; Tavandashti, Zoleykha; Paradies, Jan (SynOpen)
In recent years, frustrated Lewis pairs have been widely used in small molecules activation and catalytic transformations. This graphic review is aimed to provide the fundamental understanding of frustrated Lewis pair reactivity and the exploitation thereof in catalytic reactions.
Keywords: Organic Chemistry; Materials Science (miscellaneous); Biomaterials; Catalysis

Stability of DNA Origami Nanostructures in Physiological Media: The Role of Molecular Interactions - Linko, Veikko; Keller, Adrian (Small)
Keywords: Biomaterials; Biotechnology; General Materials Science; General Chemistry

Environment‐Dependent Stability and Mechanical Properties of DNA Origami Six‐Helix Bundles with Different Crossover Spacings - Xin, Yang; Piskunen, Petteri; Suma, Antonio; Li, Changyong; Ijäs, Heini; Ojasalo, Sofia; Seitz, Iris; Kostiainen, Mauri A.; Grundmeier, Guido; Linko, Veikko; Keller, Adrian (Small)
Keywords: Biomaterials; Biotechnology; General Materials Science; General Chemistry

Formation of insoluble silver-phases in an iron-manganese matrix for bioresorbable implants using varying laser beam melting strategies - Krüger, Jan Tobias; Hoyer, Kay-Peter; Hengsbach, Florian; Schaper, Mirko (Journal of Materials Research and Technology)
Keywords: Metals and Alloys; Surfaces; Coatings and Films; Biomaterials; Ceramics and Composites

Combined in-situ attenuated total reflection-Fourier transform infrared spectroscopy and single molecule force studies of poly(acrylic acid) at electrolyte/oxide interfaces at acidic pH - Neßlinger, Vanessa; Orive, Alejandro G.; Meinderink, Dennis; Grundmeier, Guido (Journal of Colloid and Interface Science)
Keywords: Colloid and Surface Chemistry; Surfaces; Coatings and Films; Biomaterials; Electronic; Optical and Magnetic Materials

Electronic Structures of Group III–V Element Haeckelite Compounds: A Novel Family of Semiconductors, Dirac Semimetals, and Topological Insulators - Khazaei, Mohammad; Ranjbar, Ahmad; Kang, Yoon‐Gu; Liang, Yunye; Khaledialidusti, Rasoul; Bae, Soungmin; Raebiger, Hannes; Wang, Vei; Han, Myung Joon; Mizoguchi, Hiroshi; Bahramy, Mohammad S.; Kühne, Thomas; et al. (Advanced Functional Materials)
Keywords: Electrochemistry; Condensed Matter Physics; Biomaterials; Electronic; Optical and Magnetic Materials

Hydrogel-Based Biosensors - Völlmecke, Katharina; Afroz, Rowshon; Bierbach, Sascha; Brenker, Lee Josephine; Frücht, Sebastian; Glass, Alexandra; Giebelhaus, Ryland; Hoppe, Axel; Kanemaru, Karen; Lazarek, Michal; Rabbe, Lukas; Song, Longfei; et al. (Gels)
There is an increasing interest in sensing applications for a variety of analytes in aqueous environments, as conventional methods do not work reliably under humid conditions or they require complex equipment with experienced operators. Hydrogel sensors are easy to fabricate, are incredibly sensitive, and have broad dynamic ranges. Experiments on their robustness, reliability, and reusability have indicated the possible long-term applications of these systems in a variety of fields, including disease diagnosis, detection of pharmaceuticals, and in environmental testing. It is possible to produce hydrogels, which, upon sensing a specific analyte, can adsorb it onto their 3D-structure and can therefore be used to remove them from a given environment. High specificity can be obtained by using molecularly imprinted polymers. Typical detection principles involve optical methods including fluorescence and chemiluminescence, and volume changes in colloidal photonic crystals, as well as electrochemical methods. Here, we explore the current research utilizing hydrogel-based sensors in three main areas: (1) biomedical applications, (2) for detecting and quantifying pharmaceuticals of interest, and (3) detecting and quantifying environmental contaminants in aqueous environments.
Keywords: Polymers and Plastics; Organic Chemistry; Biomaterials; Bioengineering

Targeted Synthesis of the Type-A Particle Substructure from Enzymatically Produced Eumelanin - Büngeler, Anne; Kollmann, Fabian; Huber, Klaus; Strube, Oliver I. (Biomacromolecules)
Keywords: Materials Chemistry; Polymers and Plastics; Biomaterials; Bioengineering

Stiffness optimization and reliable design of a hip implant by using the potential of additive manufacturing processes - Risse, Lena; Woodcock, Steven Clifford; Brüggemann, Jan-Peter; Kullmer, Gunter; Richard, Hans Albert (BioMedical Engineering OnLine)
Abstract Background Due to the steadily increasing life expectancy of the population, the need for medical aids to maintain the previous quality of life is growing. The basis for independent mobility is a functional locomotor system. The hip joint can be so badly damaged by everyday wear or accelerated by illness that reconstruction by means of endoprostheses is necessary. Results In order to ensure a high quality of life for the patient after this procedure as well as a long service life of the prosthesis, a high-quality design is required, so that many different aspects have to be taken into account when developing prostheses. Long-term medical studies show that the service life and operational safety of a hip prosthesis by best possible adaptation of the stiffness to that of the bone can be increased. The use of additive manufacturing processes enables to specifically change the stiffness of implant structures. Conclusions Reduced implant stiffness leads to an increase in stress in the surrounding bone and thus to a reduction in bone resorption. Numerical methods are used to demonstrate this fact in the hip implant developed. The safety of use is nevertheless ensured by evaluating and taking into account the stresses that occur for critical load cases. These results are a promising basis to enable longer service life of prostheses in the future.
Keywords: Radiology; Nuclear Medicine and imaging; Biomedical Engineering; General Medicine; Biomaterials; Radiological and Ultrasound Technology

FeMn with Phases of a Degradable Ag Alloy for Residue-Free and Adapted Bioresorbability - Krüger, Jan Tobias; Hoyer, Kay-Peter; Huang, Jingyuan; Filor, Viviane; Mateus-Vargas, Rafael Hernan; Oltmanns, Hilke; Meißner, Jessica; Grundmeier, Guido; Schaper, Mirko (Journal of Functional Biomaterials)
The development of bioresorbable materials for temporary implantation enables progress in medical technology. Iron (Fe)-based degradable materials are biocompatible and exhibit good mechanical properties, but their degradation rate is low. Aside from alloying with Manganese (Mn), the creation of phases with high electrochemical potential such as silver (Ag) phases to cause the anodic dissolution of FeMn is promising. However, to enable residue-free dissolution, the Ag needs to be modified. This concern is addressed, as FeMn modified with a degradable Ag-Calcium-Lanthanum (AgCaLa) alloy is investigated. The electrochemical properties and the degradation behavior are determined via a static immersion test. The local differences in electrochemical potential increase the degradation rate (low pH values), and the formation of gaps around the Ag phases (neutral pH values) demonstrates the benefit of the strategy. Nevertheless, the formation of corrosion-inhibiting layers avoids an increased degradation rate under a neutral pH value. The complete bioresorption of the material is possible since the phases of the degradable AgCaLa alloy dissolve after the FeMn matrix. Cell viability tests reveal biocompatibility, and the antibacterial activity of the degradation supernatant is observed. Thus, FeMn modified with degradable AgCaLa phases is promising as a bioresorbable material if corrosion-inhibiting layers can be diminished.
Keywords: Biomedical Engineering; Biomaterials

FeMn with Phases of a Degradable Ag Alloy for Residue-Free and Adapted Bioresorbability - Krüger, Jan Tobias; Hoyer, Kay-Peter; Huang, Jingyuan; Filor, Viviane; Mateus-Vargas, Rafael Hernan; Oltmanns, Hilke; Meißner, Jessica; Grundmeier, Guido; Schaper, Mirko (Journal of Functional Biomaterials)
The development of bioresorbable materials for temporary implantation enables progress in medical technology. Iron (Fe)-based degradable materials are biocompatible and exhibit good mechanical properties, but their degradation rate is low. Aside from alloying with Manganese (Mn), the creation of phases with high electrochemical potential such as silver (Ag) phases to cause the anodic dissolution of FeMn is promising. However, to enable residue-free dissolution, the Ag needs to be modified. This concern is addressed, as FeMn modified with a degradable Ag-Calcium-Lanthanum (AgCaLa) alloy is investigated. The electrochemical properties and the degradation behavior are determined via a static immersion test. The local differences in electrochemical potential increase the degradation rate (low pH values), and the formation of gaps around the Ag phases (neutral pH values) demonstrates the benefit of the strategy. Nevertheless, the formation of corrosion-inhibiting layers avoids an increased degradation rate under a neutral pH value. The complete bioresorption of the material is possible since the phases of the degradable AgCaLa alloy dissolve after the FeMn matrix. Cell viability tests reveal biocompatibility, and the antibacterial activity of the degradation supernatant is observed. Thus, FeMn modified with degradable AgCaLa phases is promising as a bioresorbable material if corrosion-inhibiting layers can be diminished.
Keywords: Biomedical Engineering; Biomaterials

FeMn with Phases of a Degradable Ag Alloy for Residue-Free and Adapted Bioresorbability - Krüger, Jan Tobias; Hoyer, Kay-Peter; Huang, Jingyuan; Filor, Viviane; Mateus-Vargas, Rafael Hernan; Oltmanns, Hilke; Meißner, Jessica; Grundmeier, Guido; Schaper, Mirko (Journal of Functional Biomaterials)
The development of bioresorbable materials for temporary implantation enables progress in medical technology. Iron (Fe)-based degradable materials are biocompatible and exhibit good mechanical properties, but their degradation rate is low. Aside from alloying with Manganese (Mn), the creation of phases with high electrochemical potential such as silver (Ag) phases to cause the anodic dissolution of FeMn is promising. However, to enable residue-free dissolution, the Ag needs to be modified. This concern is addressed, as FeMn modified with a degradable Ag-Calcium-Lanthanum (AgCaLa) alloy is investigated. The electrochemical properties and the degradation behavior are determined via a static immersion test. The local differences in electrochemical potential increase the degradation rate (low pH values), and the formation of gaps around the Ag phases (neutral pH values) demonstrates the benefit of the strategy. Nevertheless, the formation of corrosion-inhibiting layers avoids an increased degradation rate under a neutral pH value. The complete bioresorption of the material is possible since the phases of the degradable AgCaLa alloy dissolve after the FeMn matrix. Cell viability tests reveal biocompatibility, and the antibacterial activity of the degradation supernatant is observed. Thus, FeMn modified with degradable AgCaLa phases is promising as a bioresorbable material if corrosion-inhibiting layers can be diminished.
Keywords: Biomedical Engineering; Biomaterials

Formation of insoluble silver-phases in an iron-manganese matrix for bioresorbable implants using varying laser beam melting strategies - Krüger, Jan Tobias; Hoyer, Kay-Peter; Hengsbach, Florian; Schaper, Mirko (Journal of Materials Research and Technology)
Keywords: Metals and Alloys; Surfaces; Coatings and Films; Biomaterials; Ceramics and Composites

Formation of insoluble silver-phases in an iron-manganese matrix for bioresorbable implants using varying laser beam melting strategies - Krüger, Jan Tobias; Hoyer, Kay-Peter; Hengsbach, Florian; Schaper, Mirko (Journal of Materials Research and Technology)
Keywords: Metals and Alloys; Surfaces; Coatings and Films; Biomaterials; Ceramics and Composites

Development of a test method for investigating the leak tightness of hybrid joined battery housing connections - Schmolke, Tobias; Teutenberg, Dominik; Meschut, Gerson (International Journal of Adhesion and Adhesives)
Keywords: Polymers and Plastics; General Chemical Engineering; Biomaterials

A combinatorial study of electrochemical anion intercalation into graphite - Chugh, Manjusha; Jain, Mitisha; Wang, Gang; Nia, Ali Shaygan; Mirhosseini, Hossein; Kühne, Thomas (Materials Research Express)
Abstract Dual-ion batteries are considered to be an emerging viable energy storage technology owing to their safety, high power capability, low cost, and scalability. Intercalation of anions into a graphite positive electrode provides high operating voltage and improved energy density to such dual-ion batteries. In this work, we have performed a combinatorial study of graphite intercalation compounds considering four anions, namely hexafluorophosphate (PF <?CDATA ${}_{6}^{-}$?> 6 − ), perchlorate (ClO <?CDATA ${}_{4}^{-}$?> 4 − ), bis(fluorosulfonyl)imide (FSI − ), and bis(trifluoromethanesulfonyl)imide (TFSI − ), via first-principles calculations. The structural properties and energetics of the intercalation compounds are compared based on different sizes, geometries, and the physical and chemical properties of the intercalated anions. The staging mechanism of anion intercalation into graphite and the specific capacities, and voltage profiles of the intercalated compounds are investigated. A comparison regarding battery electrochemistry is also done with available experimental observations. Our calculated intercalation energies and voltage profiles show that the initial anion intercalation into graphite is less favorable than subsequent ones for all the anions considered in this study. Although the effect of the size of anions in a graphite cathode on various properties of the intercalated compounds is not as significant as the size of cations in a graphite anode, some distinction between the studied anions can still be made. Among the studied anions, the intercalation compounds based on PF <?CDATA ${}_{6}^{-}$?> 6 − are the most stable ones. These PF <?CDATA ${}_{6}^{-}$?> 6 − anions cause relatively small structural deformations of the graphite and have the highest oxidative ability, highest onset voltage, and highest diffusion barrier along the graphene sheets. The overall small diffusion barriers of the anions within graphite explain the high rate capability of dual-ion batteries.
Keywords: Metals and Alloys; Polymers and Plastics; Surfaces; Coatings and Films; Biomaterials; Electronic; Optical and Magnetic Materials

Ultrahigh water sorption on highly nitrogen doped carbonaceous materials derived from uric acid - Kossmann, Janina; Rothe, Regina; Heil, Tobias; Antonietti, Markus; Lopez Salas, Nieves (Journal of Colloid and Interface Science)
Keywords: Colloid and Surface Chemistry; Surfaces; Coatings and Films; Biomaterials; Electronic; Optical and Magnetic Materials

Self-Assembled Fibrinogen Hydro- and Aerogels with Fibrin-like 3D Structures - Hense, Dominik; Büngeler, Anne; Kollmann, Fabian; Hanke, Marcel; Orive, Alejandro; Keller, Adrian; Grundmeier, Guido; Huber, Klaus; Strube, Oliver I. (Biomacromolecules)
Keywords: Materials Chemistry; Polymers and Plastics; Biomaterials; Bioengineering

Resource‐Efficient Low‐Temperature Synthesis of Microcrystalline Pb2B5O9X (X = Cl, Br) for Surfaces Studies by Optical Second Harmonic Generation - Tan, Deming; Kirbus, Benjamin; Rüsing, Michael; Pietsch, Tobias; Ruck, Michael; Eng, Lukas M. (Small)
Optically nonlinear Pb2B5O9X (X = Cl, Br) borate halides are an important group of materials for second harmonic generation (SHG). Additionally, they also possess excellent photocatalytic activity and stability in the process of dechlorination of chlorophenols, which are typical persistent organic pollutants. It would be of great interest to conduct in situ (photo‐) catalysis investigations during the whole photocatalytic process by SHG when considering them as photocatalytic materials. In order to get superior photocatalytic efficiency and maximum surface information, small particles are highly desired. Here, a low‐cost and fast synthesis route that allows growing microcrystalline optically nonlinear Pb 2 B 5 O 9 X borate halides at large quantities is introduced. When applying the ionothermal growth process at temperatures between 130 and 170 °C, microcrystallites with an average size of about 1 µm precipitate with an orthorhombic hilgardite‐like borate halide structure. Thorough examinations using powder X‐ray diffraction and scanning electron microscopy, the Pb2B5O9X microcrystals are indicated to be chemically pure and single‐phased. Besides, the Pb2B5O9X borate halides' SHG efficiencies are confirmed using confocal SHG microscopy. The low‐temperature synthesis route thus makes these borate halides a highly desirable material for surface studies such as monitoring chemical reactions with picosecond time resolution and in situ (photo‐) catalysis investigations.
Keywords: Biomaterials; Biotechnology; General Materials Science; General Chemistry

The Twofold Role of 12-Hydroxyoctadecanoic Acid (12-HOA) in a Ternary Water—Surfactant—12-HOA System: Gelator and Co-Surfactant - Steck, Katja; Schmidt, Claudia; Stubenrauch, Cosima (Gels)
Gelled lyotropic liquid crystals can be formed by adding a gelator to a mixture of surfactant and solvent. If the gel network and the liquid-crystalline phase coexist without influencing each other, the self-assembly is called orthogonal. In this study, the influence of the organogelator 12-hydroxyoctadecanoic acid (12-HOA) on the lamellar and hexagonal liquid crystalline phases of the binary system H2O–C12E7 (heptaethylene glycol monododecyl ether) is investigated. More precisely, we added 12-HOA at mass fractions from 0.015 to 0.05 and studied the resulting phase diagram of the system H2O–C12E7 by visual observation of birefringence and by 2H NMR spectroscopy. In addition, the dynamic shear moduli of the samples were measured in order to examine their gel character. The results show that 12-HOA is partly acting as co-surfactant, manifested by the destabilization of the hexagonal phase and the stabilization of the lamellar phase. The higher the total surfactant concentration, the more 12-HOA is incorporated in the surfactant layer. Accordingly, its gelation capacity is substantially reduced in the surfactant solution compared to the system 12-HOA–n-decane, and large amounts of gelator are required for gels to form, especially in the lamellar phase.
Keywords: Polymers and Plastics; Organic Chemistry; Biomaterials; Bioengineering

Liquid crystalline dithienothiophene derivatives for organic electronics - Vollbrecht, Joachim; Oechsle, Peter; Stepen, Arne; Hoffmann, Florian; Paradies, Jan; Meyers, Thorsten; Hilleringmann, Ulrich; Schmidtke, Jürgen; Kitzerow, Heinz (Organic Electronics)
Keywords: Electrical and Electronic Engineering; Materials Chemistry; Condensed Matter Physics; General Chemistry; Biomaterials; Electronic; Optical and Magnetic Materials

Alignment and Graphene-Assisted Decoration of Lyotropic Chromonic Liquid Crystals Containing DNA Origami Nanostructures - Martens, Kevin; Funck, Timon; Kempter, Susanne; Roller, Eva-Maria; Liedl, Tim; Blaschke, Benno M.; Knecht, Peter; Garrido, José Antonio; Zhang, Bingru; Kitzerow, Heinz-Siegfried (Small)
Keywords: Biomaterials; Biotechnology; General Materials Science; General Chemistry

On the selective aerobic oxidation of benzyl alcohol with Pd/Au-nanoparticles in batch and flow - Alex, Hannes; Steinfeldt, Norbert; Jähnisch, Klaus; Bauer, Matthias; Hübner, Sandra (Nanotechnology Reviews)
Abstract Nanoparticles (NP) have specific catalytic properties, which are influenced by parameters like their size, shape, or composition. Bimetallic NPs, composed of two metal elements can show an improved catalytic activity compared to the monometallic NPs. We, herein, report on the selective aerobic oxidation of benzyl alcohol catalyzed by unsupported Pd/Au and Pd NPs at atmospheric pressure. NPs of varying compositions were synthesized and characterized by UV/Vis spectroscopy, transmission electron microscopy (TEM), and small-angle X-ray scattering (SAXS). The NPs were tested in the model reaction regarding their catalytic activity, stability, and recyclability in batch and continuous procedure. Additionally, in situ extended X-ray absorption fine structure (EXAFS) measurements were performed in order to get insight in the process during NP catalysis.
Keywords: Surfaces; Coatings and Films; Process Chemistry and Technology; Energy Engineering and Power Technology; Biomaterials; Medicine (miscellaneous); Biotechnology

Embedding DNA in surfactant mesophases: The phase diagram of the ternary system dodecyltrimethylammonium–DNA/monoolein/water in comparison to the DNA-free analogue - Bilalov, Azat; Elsing, Jonas; Haas, Eva; Schmidt, Claudia; Olsson, Ulf (Journal of Colloid and Interface Science)
Keywords: Colloid and Surface Chemistry; Surfaces; Coatings and Films; Biomaterials; Electronic; Optical and Magnetic Materials

Effect of shear on vesicle and lamellar phases of DDAB/lecithin ternary systems - Youssry, Mohamed; Coppola, Luigi; Nicotera, Isabella; Ar, Gönül; Schmidt, Claudia (Journal of Colloid and Interface Science)
Keywords: Colloid and Surface Chemistry; Surfaces; Coatings and Films; Biomaterials; Electronic; Optical and Magnetic Materials

EXAFS as Powerful Analytical Tool for the Investigation of Organic-Inorganic Hybrid Materials - Gross, Silvia; Bauer, Matthias (Advanced Functional Materials)
Keywords: Electrochemistry; Condensed Matter Physics; Biomaterials; Electronic; Optical and Magnetic Materials

Functional Chromium Wheel-Based Hybrid Organic-Inorganic Materials for Dielectric Applications - Di Noto, Vito; Boeer, Angelika B.; Lavina, Sandra; Muryn, Christopher A.; Bauer, Matthias; Timco, Grigore A.; Negro, Enrico; Rancan, Marzio; Winpenny, Richard E. P.; Gross, Silvia (Advanced Functional Materials)
Keywords: Electrochemistry; Condensed Matter Physics; Biomaterials; Electronic; Optical and Magnetic Materials

Microemulsion approach to neodymium, europium, and ytterbium oxide/hydroxide colloids—Effects of precursors and preparation parameters on particle size and crystallinity - Rill, Christoph; Bauer, Matthias; Bertagnolli, Helmut; Kickelbick, Guido (Journal of Colloid and Interface Science)
Keywords: Colloid and Surface Chemistry; Surfaces; Coatings and Films; Biomaterials; Electronic; Optical and Magnetic Materials

Coexisting lamellar phases in water–oil–surfactant systems induced by the addition of an amphiphilic block copolymer - Frank, Christian; Strey, Reinhard; Schmidt, Claudia; Stubenrauch, Cosima (Journal of Colloid and Interface Science)
Keywords: Colloid and Surface Chemistry; Surfaces; Coatings and Films; Biomaterials; Electronic; Optical and Magnetic Materials

Colloid–polymer mixtures in solution with refractive index matched acrylate colloids - Kramer, Thomas; Scholz, Stephanie; Maskos, Michael; Huber, Klaus (Journal of Colloid and Interface Science)
Keywords: Colloid and Surface Chemistry; Surfaces; Coatings and Films; Biomaterials; Electronic; Optical and Magnetic Materials

A Doubly Branched Nonionic Oligooxyethylene V-Amphiphile: Effect of Molecular Geometry on Liquid-Crystalline Phase Behavior, 3 - Kratzat, Krystyna; Schmidt, Claudia; Finkelmann, Heino (Journal of Colloid and Interface Science)
Keywords: Colloid and Surface Chemistry; Surfaces; Coatings and Films; Biomaterials; Electronic; Optical and Magnetic Materials

Characterization of Worm-like Micelles Containing Solubilized Dye-Molecules by Light Scattering Techniques - Herzog, Bernd; Huber, Klaus; Rennie, Adrian R. (Journal of Colloid and Interface Science)
Keywords: Colloid and Surface Chemistry; Surfaces; Coatings and Films; Biomaterials; Electronic; Optical and Magnetic Materials

Mixtures of Polyacrylic Acid and Nonionic Surfactants at the Water/Air Interface - Maloney, Colette; Huber, Klaus (Journal of Colloid and Interface Science)
Keywords: Colloid and Surface Chemistry; Surfaces; Coatings and Films; Biomaterials; Electronic; Optical and Magnetic Materials

Interactions in mixed interfaces of binary surfactant solutions - Huber, Klaus (Journal of Colloid and Interface Science)
Keywords: Colloid and Surface Chemistry; Surfaces; Coatings and Films; Biomaterials; Electronic; Optical and Magnetic Materials